Efektivitas Teknik Self Regulated Learning Dalam Meningkatkan Kemandirian Belajar Siswa - Fatimah Ibda (Universitas Muhammadiyah Metro, 2025)
Learning independence is an essential aspect of students’ academic development, particularly at the senior high school level, as it enables students to manage their learning processes, set goals, and take responsibility for their academic outcomes. One approach that has been widely recognized for fostering learning independence is Self-Regulated Learning (SRL), which emphasizes students’ ability to plan, monitor, and evaluate their own learning activities. This study aimed to examine the effectiveness of the application of Self-Regulated Learning techniques in improving students’ learning independence. The study was conducted at SMAN 5 Banda Aceh using a quantitative approach with a one-group pretest–posttest design. The research sample consisted of 36 senior high school students. Data were collected using questionnaires measuring learning independence and self-regulated learning, and the data were analyzed using a t-test. The results showed a significant difference between pretest scores (M = 70.31) and posttest scores (M = 77.15), with a t value of 5.127 and a significance level of 0.000 (p < 0.05). These findings indicate that the implementation of Self-Regulated Learning techniques is effective in increasing students’ learning independence. The improvement was reflected in a shift in students’ learning independence levels from low to moderate and high categories. This study provides empirical evidence that SRL can be effectively applied as a strategy within guidance and counseling services to promote students’ autonomy in learning. The findings suggest that consistent application of SRL techniques can help students develop better self-management skills, enhance motivation, and foster responsible learning behaviors that are essential for long-term academic success.